2015
DOI: 10.1016/j.yebeh.2015.01.006
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral changes following a single episode of early-life seizures support the latent development of an autistic phenotype

Abstract: We probed the developmental and behavioral consequences of a single early life seizure induced by kainic acid (KA-ELS) in the rat on post natal day 7. Correlates of developmental trajectory were not altered, demonstrating that long term consequences following KA-ELS are not initiated by secondary causes, such as malnourishment or alterations in maternal care. We report reduced marble burying in adult rats, suggestive of restricted interests, a trait common to experimental and clinical autism. We did not detect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 62 publications
3
22
0
Order By: Relevance
“…However, it is necessary to interpret these findings cautiously when underlying etiological factors of seizures are not taken into account, control groups are lacking, or a selected cohort consists only of infants with very low birthweight . While some long‐term preclinical studies with animal models have suggested that seizures in immature brains may cause epileptogenesis and cognitive deficits, they also suffer from inherent limitations such as a selected pathology to increased seizure susceptibilities, variant postnatal age and different central nervous system ontogenic schedules between species, and various ways of inducing seizures in the laboratory . In contrast, we attempted to isolate the neurological sequelae attributable to neonatal seizures per se from those arising from underlying pathological conditions in a real‐world setting.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is necessary to interpret these findings cautiously when underlying etiological factors of seizures are not taken into account, control groups are lacking, or a selected cohort consists only of infants with very low birthweight . While some long‐term preclinical studies with animal models have suggested that seizures in immature brains may cause epileptogenesis and cognitive deficits, they also suffer from inherent limitations such as a selected pathology to increased seizure susceptibilities, variant postnatal age and different central nervous system ontogenic schedules between species, and various ways of inducing seizures in the laboratory . In contrast, we attempted to isolate the neurological sequelae attributable to neonatal seizures per se from those arising from underlying pathological conditions in a real‐world setting.…”
Section: Discussionmentioning
confidence: 99%
“…Early life seizures can be modeled in rodents using convulsants, and there is compelling evidence for long‐term effects on cognition . In addition, early life seizures were also found to cause deficits in some, but not all, ASD‐like behaviors, largely revealed as deficits in social interactions …”
Section: Epilepsy and Autismmentioning
confidence: 99%
“…This result, in part, contrasted findings reported in adult rats that had undergone one prior episode of KAinduced status epilepticus initiated on P7. As adults, males spent less time in the zone with the animal trap but more time sniffing the stranger rat compared to controls [44].…”
Section: Social Behaviormentioning
confidence: 88%